Comparison of the Multiple Mini-Interview and the Traditional Interview in Medical School Admissions: Lessons Learned Using a Hybrid Model at One Institution. (22nd December 2022) - Abrams, Madeline; Olvet, Doreen M.; Ellenbogen, Lisa; Bird, Jeffrey B.; Fazio, Christopher; Caprioglio, Lauren; Ginzburg, Samara; Smith, Lawrence; Woldenberg, Rona
Abstract : Purpose: Medical school admissions interviews are a critical form of assessment; however, the most effective interview strategy is debated. This study compares the traditional interview (TI) and multiple mini-interview (MMI) within a hybrid TI-MMI model at one medical school to determine whether the interview approaches reveal different information about applicants and whether a hybrid model results in a more diversified applicant pool. Method: Admissions data from 3 application cycles at the Donald and Barbara Zucker School of Medicine at Hofstra/Northwell were used. The TI was used in 2017–2018 and the hybrid TI-MMI model in 2018–2019 and 2019–2020. Applicants were scored on a 5-point scale and referred to a voting committee for acceptance consideration if interview scores met threshold criteria. Changes in the number of students referred to the committee using the TI vs the TI-MMI score criteria were analyzed. Results: In 2017–2018 (TI only), 683 applicants were interviewed; in 2018–2019 (TI-MMI), 844 applicants were interviewed; and in 2019–2020 (TI-MMI), 805 applicants were interviewed. Medium correlations were found between total MMI and TI scores in 2018–2019 ( ρ = 0.37, P < .001) and 2019–2020 ( ρ = 0.33, P < .001). No differences were found in TI scores between 2017–2018 and 2018–2019 ( P = .30), but TI scores were significantly lower in 2019–2020 vs 2017–2018 ( P < .001) and 2018–2019 ( P = .002). Overall, a 10% to 18% increase was found in the number of applicants referred to the voting committee when using hybrid criteria, with a 19% to 27% increase in underrepresented in medicine applicants. Conclusions: The TI-MMI model may allow for a more holistic interview approach and an expanded pool of applicants, particularly underrepresented in medicine applicants, considered for acceptance.